Analysis of Application of Village Fund Allocation in Efforts to Increase Development in Titi Papan Village, Medan Deli District - Aisyah Aisyah; Mawaddah Irham (Penerbit Jurnal Indonesia, 2022)
The ADD (Village Fund Allocation) program is one part of the APBD which is allocated to meet needs, the role of the government, and to support village development. The ADD program is one source of income that can be linked to support village development in order to improve the welfare of rural communities. This study aims to determine the implementation of the ADD program in an effort to increase rural growth. This research is a qualitative research. The results showed that the village government had properly implemented the ADD program standards based on the North Minahasa Regional Regulation No. 22 of 2016.